New Sharp Ostrowski-type Inequalities and Generalized Trapezoid-type Inequalities for Riemann–Stieltjes Integrals and their Applications - Alomari, M.W. (Український математичний журнал, 2013)
We prove new sharp weighted generalizations of Ostrowski-type and generalized trapezoid-type inequalities for Riemann–Stieltjes integrals. Several related inequalities are deduced and investigated. New Simpson-type inequalities are obtained for the RS-integral. Finally, as an application, we estimate the error of a general quadrature rule for the RS-integral via the Ostrowski–generalized-trapezoid-quadrature formula. Доведено нові точні зважені узагальнення нєрівностєй типу Островського та типу узагальненого трапецоїда для iнтегралiв Рімана-Стільтьєса. Отримано та досліджено кілька близьких нерівностей. Отримано нові нерівності типу Сімпсона для RS -інтеграла. Як застосування наведено оцінку похибки загального правила квадратур для RS -інтеграла із використанням квадратурної формули Островського — узагальненого трапецоїда.